Middle-Passive Constructions, Dative Possessors, and Word Order in Spanish - Imanol Suárez-Palma (Languages, 2023)
This paper examines data from Spanish middle-passive sentences whose grammatical subject contains a body-part noun, externally possessed by means of a dative possessor. I advocate for an analysis whereby the possessor originates inside the theme DP and raises to the specifier of an applicative projection to be licensed with dative case. I show that the unmarked order for dative DPs in these configurations is preverbal. These phrases may appear as the sole preverbal constituent, presumably in preverbal subject position, thus forcing the theme DP to remain inside the VP; alternatively, both the dative DP and theme DP can occur preverbally, in which case, the former appears to be left dislocated while the latter would be probed to preverbal subject position. This last scenario leads to a minimality violation, since the theme would be probed over the empty pronominal standing for the possessor that must necessarily sit in Spec, ApplP for the inalienable possession construal to obtain. Instead, I argue that both preverbal dative and theme DPs in Spanish middle-passive sentences are left dislocated and corefer with empty pronominals inside the sentence; the null dative possessor, being closer to T° always raises to subject position, which avoids any potential intervention effects. Finally, I explore how these data can be analyzed within a paratactic approach.